(untitled) (Proceedings of International Educators Conference, 2022)
The theme of the hero in world literature has occupied a central place for many centuries. It is for this reason that the field of literature entered our hearts in our lives. Innovations in the field of literature, the interaction of our national literature, and cooperation are growing in our country. Reading books expands our worldview, encourages deep reflection and makes us think clearly and deeply. It won’t be wrong to say that books are the key to success. Today, the life experience of a person who reads books is increasing. But to learn from this work of positive characters, you need to read thousands of works. The ability to make the right choice means the ability to find answers to complex tests.